Novel extended pi-conjugated Zn(II)-porphyrin derivatives bearing pendant triphenylamine moiety for dye-sensitized solar cell: synthesis and characterization - Kang, Min Soo; Oh, Jae Buem; Seo, Kang Deuk; Kim, Hwan Kyu; Park, Jihee; Kim, Kyoungkon; Park, Nam-Gyu (WORLD SCI PUBL CO INC, 2009)
We have designed and synthesized novel Zn(II)-porphyrin derivatives for dye-sensitized solar cells. The derivatives incorporate the electron-donating group of a pendant triphenylamine into cyano-substituted ([TPA] Zn-Por-CN1) or non-substituted stilbene moiety ([TPA] Zn-Por1) in the 5,10,15-meso- position and carboxylic acid group in the 20-meso-position in a porphyrin derivative. Their chemical structures were characterized by H-1 NMR, FT-IR, UV-vis absorption, EI-mass, and MALDI-TOF mass spectroscopies. Their electrochemical properties were studied by cyclic voltammetry measurement. These Zn(II)-porphyrin derivatives have been used to fabricate dye-sensitized solar cells based on I-/I-2 liquid electrolytes as dye sensitizers and their device performances were evaluated by comparing with that of a standard Ru(II) complex dye. [TPA] Zn-Por-CN1 showed higher power conversion efficiency than that of [TPA] Zn-Por1, due to a broader absorption band around 435 nm. Short-circuit photocurrent density (J(sc)), open-circuit voltage (V-oc), fill factor (FF), and power conversion efficiency (eta) of DSSC for [TPA] Zn-Por-CN1 were evaluated to be J(sc) = 6.3 mA.cm(-2), V-oc = 0.737 V, FF = 0.683, and eta = 3.1%, respectively.
Keywords: CHARGE-TRANSFER SENSITIZERS; NANOCRYSTALLINE TIO2; COMPLEXES; METALLOPORPHYRINS; ENHANCEMENT; CONVERSION; LIGHT; IR